ENGLISH LANGUAGE IN THE CONTEXT OF DISTANCE LEARNING - Osilpashsha Raximbayeva Shermat qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  rapid  development  of  digital  technologies  has  significantly transformed  the  field  of  education,  particularly  in  the  teaching  and  learning  of  the English language. Distance learning has become an essential component of modern education, enabling students to access learning materials and participate in educational activities  regardless  of  geographical  location.  This  study  explores  the  role  of  the English  language  in the  context of distance  learning, focusing  on  its  effectiveness, challenges, and opportunities for both teachers and learners. The research analyzes how online platforms, virtual classrooms, and digital communication tools facilitate English language acquisition and improve students’ language skills, including reading, writing, listening, and speaking. The study also highlights several challenges associated with distance learning, such as technological barriers and reduced face-to-face interaction. The findings suggest that when supported by appropriate technological infrastructure and effective teaching methods, distance learning can significantly enhance the process of English language acquisition.